HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP KELUARGA PASIEN TERHADAP TINDAKAN RESUSITASI JANTUNG PARU (RJP) - Nusroh, Ninik Nailun (STIKES Widyagama Husada, 2025)
Cardiopulmonary resuscitation is an action carried out to restore and maintain the function of vital organs in patients with cardiac arrest and respiratory arrest. The knowledge and attitudes of the patient's family greatly influence the results of the RJP action. This study aims to determine the relationship between the level of knowledge and the attitude of the patient's family towards cardiopulmonary resuscitation (CPR). This research is a quantitative study with a correlation design and applies a cross-sectional approach. Sampling used nonprobability sampling (purposive sampling), with a total of 68 respondents. Data collection was carried out using a questionnaire and recording it on an observation sheet. In the knowledge level data, the result was that the majority of respondents had a poor level of knowledge, 38 respondents (55.9%), and in the attitude data, the result was that the majority of respondents had a poor attitude towards RJP actions, 40 respondents (58.8%). Statistical results show that there is a relationship between the level of knowledge and the attitude of the patient's family towards CPR, which obtained a significance value of 0.000 (p<0.05). Most of the patient's family knowledge is lacking due to the level of education and age which influence the results of the CPR procedure.